2019
DOI: 10.1007/s12350-018-1232-9
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and variability in reporting of clinically actionable incidental findings on attenuation-correction CT scans in a veteran population

Abstract: Incidental noncardiac findings on CTACs are common in our veteran population. Overall interobserver agreement in identifying these findings between cardiologists and radiologists is fair. Specific guidelines are needed on how CTACs should be read and reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…We agree with the conclusions of He et al 1 regarding the need for a greater degree of training for specialists primarily aligned with adult internal medicine, rather than radiology, to ensure appropriate reporting of important incidental findings on attenuation-correction CT images in myocardial perfusion imaging (MPI). In Australia, MPI studies are reported by Nuclear Medicine specialists who are accredited by the Australasian Association of Nuclear Medicine Specialists (AANMS).…”
Section: Letter To the Editor Pulmonary Nodules Incidentally Detectedsupporting
confidence: 88%
“…We agree with the conclusions of He et al 1 regarding the need for a greater degree of training for specialists primarily aligned with adult internal medicine, rather than radiology, to ensure appropriate reporting of important incidental findings on attenuation-correction CT images in myocardial perfusion imaging (MPI). In Australia, MPI studies are reported by Nuclear Medicine specialists who are accredited by the Australasian Association of Nuclear Medicine Specialists (AANMS).…”
Section: Letter To the Editor Pulmonary Nodules Incidentally Detectedsupporting
confidence: 88%
“…Images were acquired at 2. 5 thickness, 120kEV and 200 mA using a 50-cm field of view, and subsequently analyzed on a dedicated CT workstation (GE AW4.4). All CT images were read by a board-certified radiologist using standard soft tissue, lung, and bone windows.…”
Section: High-dose High-resolution Spect-ctmentioning
confidence: 99%
“…The above discussion brings us to the latest study by He et al in which consecutive SPECT-CT MPI studies over an 8-month period were analyzed for noncardiac findings. 5 Both 16-and 64-slice CT scanners were used with 120KeV and 30-60 mA. Images were acquired with 3.8 (PET-CT) or 5 mm (SPECT-CT) slices.…”
Section: Cardiology Vs Radiologymentioning
confidence: 99%
“…Lee and Delaney's thoughtful comments regarding our article ''Prevalence and Variability in Reporting of Clinically Actionable Incidental Findings on Attenuation-Correction CT Scans in A Veteran Population''. 1 The primary finding from our project was that clinically significant incidental findings on CTACs are common, and there is considerable interobserver disagreement between cardiology-trained and radiology-trained physicians in identifying them, especially for pulmonary nodules. We completely agree that this discordance represents an important gap in our current practice and warrants initiatives to assure adequate training requirements and reporting standards for interpreting CTACs.…”
mentioning
confidence: 96%